Assessment of Eco Tourist Potential of Recreational Places of Samarkand Region - S.N. Sadikova; J.R. Sadikov (Universitas Muhammadiyah Sidoarjo, 2020)
The article covers some research data on the potential for the development of eco-tourism in recreational suburban places of the Samarkand region, in particular: Mirankul, Tepa-kul, Agalyk, Nurbulok, Amankutan, Dobusiya, Yukori Chinor, Ming Archa, Kattakurgan reservoir, Zarafshan river and others. The electronic social questionnaire Survey 123 Online of software ArcGIS from Esri was created to survey the local population of Uzbekistan on specific answers from various age groups of society. The author collected an opinion of local people about: favorite of the types of active and passive rest of the population in places of countryside rest places of the Samarkand region; the characterization of each of the presented country vacation spots was made public; the most popular time of year for going on nature in the Samarkand region; positive and negative features of specific suburban recreation areas were identified, most popular of them were matched on the map of the Samarkand region. The opinion of people about the most polluted recreation site of the Samarkand region and on possible method of penalization for vandalism and damage to flora and fauna in Uzbekistan was also revealed. All these data were processed in Excel, the statistical program SPSS, based on these data, charts, graphs and maps were compiled.